Breast and cervical cancer screening among women at reproductive age in Cambodia: A secondary analysis of Cambodia Demographic and Health Survey 2022 - Samnang Um; Heng Sopheab (PLoS ONE, 2025)
Breast and cervical cancers are the most prevalent diagnosed in women worldwide, significantly contributing to maternal morbidity and mortality. We examined socio-demographic and behavioral factors associated with breast and cervical cancer screening among Cambodian women aged 15–49 years old. We analyzed women’s data from the 2022 Cambodia Demographic and Health Survey (CDHS). In total, 19,496 women were interviewed. Multiple logistic regression was performed using STATA V17 to examine factors associated with breast and cervical cancer screening. The proportion of breast and cervical cancer screenings was 10.6% and 15.3%, respectively. After being adjusted, factors independently associated with breast cancer screening included age group 20–29 years [AOR = 2.51; 95% CI: 1.55–4.06], 30–39 years [AOR = 4.34; 95% CI: 2.66–7.09], and 40–49 years [AOR = 4.66; 95% CI: 2.81–7.71], higher education [AOR = 1.92; 95% CI: 1.26–2.93], exposure media [AOR = 1.66; 95% CI: 1.32–2.10], and rich wealth quintile [AOR = 1.50; 95% CI: 1.25–1.80]. Similarly, the odds of having cervical cancer screening were age group 20–29 years [AOR = 2.88; 95% CI: 1.76–4.71], 30–39 years [AOR = 5.94; 95% CI: 3.58–9.83], and 40–49 years [AOR = 7.61; 95% CI: 4.55–12.73], higher education [AOR = 1.55; 95% CI: 1.55–2.73], exposure media [AOR = 1.62; 95% CI: 1.35,1.95], and rich wealth quintile [AOR = 2.14; 95% CI: 1.78–2.5f8]. In conclusion, this study shows the low screening proportion for both breast and cervical cancers, and it also highlights that socio-economic factors are significantly important in determining the health care seeking for these two main cancer screening services among women aged 15–49 years in Cambodia. Therefore, increase of exposure media with health education focusing on these cancer screenings should be made better accessible to women, particularly those of low socio-economic status.